2019
DOI: 10.1111/jfd.12934
|View full text |Cite
|
Sign up to set email alerts
|

Effect of catecholamine stress hormones (dopamine and norepinephrine) on growth, swimming motility, biofilm formation and virulence factors of Yersinia ruckeri in vitro and an in vivo evaluation in rainbow trout

Abstract: In this study, we evaluated the impact of the catecholamines on growth, swimming motility, biofilm formation and some virulence factors activities of pathogenic Yersinia ruckeri. Norepinephrine and dopamine (at 100 µM) significantly increased the growth of Y. ruckeri in culture media containing serum. An increase in swimming motility of the pathogen was found following the exposure to the hormones; however, no effect was seen on caseinase, phospholipase and haemolysin productions. Further, antagonists for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 63 publications
2
15
0
1
Order By: Relevance
“…As motility was found to be modified in a large amount of Gram-negative bacteria after exposure to NE or Epi 13,1619 , we decided to study this effect on P. aeruginosa H103 (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As motility was found to be modified in a large amount of Gram-negative bacteria after exposure to NE or Epi 13,1619 , we decided to study this effect on P. aeruginosa H103 (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Bacteria can be exposed to a multitude of host cell molecules such as catecholamines 7 that could enhance the growth of many gram-negative bacteria 8,9,12,17,18,2326 as well as their virulence 19,27 . Till now, only few studies were conducted on the effect of these molecules on P. aeruginosa , which is an opportunistic pathogen, often found in hospital-acquired infections.…”
Section: Discussionmentioning
confidence: 99%
“…During a host stress situation, catecholamines (epinephrine, norepinephrine and dopamine), glucocorticoids (cortisol) and other stress-induced molecules (such as serotonin) are synthetized and released into blood circulation, oral cavity and gut lumen. It has been reported that these molecules can impact both in vitro and in situ the physiological behavior of bacteria, including their growth features, adhesion and/or biofilm formation capacities [ 27 , 28 , 29 , 30 , 31 , 32 ]. With the general objective to better understand the maintenance of this beneficial bacterial species within the GM, we characterized in this work the homo-aggregation, adhesion and biofilm formation capacities of 14 unrelated strains of P. distasonis and examine their response to stress molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular basis of how Y. ruckeri produces biofilms has not been investigated in detail. Biofilm formation in Y. ruckeri seems to be regulated through quorum‐sensing homoserine lactones (Torabi Delshad et al ., 2019) and by catecholamines (Torabi Delshad et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%